An economic assessment of fish polyculture as an adaptation strategy against environmental change in the southwest coastal region of Bangladesh. Issue 1 (2nd January 2021) - Basu, Sudipa; Roy, Apurba
ABSTRACT: The paper reports an evaluation of the effectiveness of fish polyculture as an adaptation strategy against environmental change in the southwest coastal region of Bangladesh. The research applies descriptive statistics, Cobb–Douglas production function model, and priority index. Simple random and convenient sampling techniques have been used to select sample and study area, respectively. The study shows that fish polyculture is economically viable and profitable. Besides, pond size, labour, and fertiliser have a significantly positive association (p < 0.05) with fish production. Virus-related mortality, salinity level, access to loans, and shrimp seedling prices are notable constraints on the fish polyculture system.